Brainstem reflex excitability after high-frequency repetitive transcranial magnetic stimulation in healthy and spinal cord injury subjects - Kumru, Hatice; Kofler, Markus; Valls-Sole, Josep; Vidal, Joan (Brain research bulletin, 2019)
•First randomized controlled trial of rTMS effects on blink reflex in SCI subjects.•High frequency rTMS modulates brainstem activity in both SCI and healthy subjects.•Dopamine release induced by rTMS may explain modulation of brainstem reflexes. The excitability of brainstem interneuronal circuits is partly under control from descending inputs. Since high frequency repetitive transcranial magnetic stimulation (rTMS) modulates cortical output, we hypothesized that it will also modulate brainstem functions. Such modulation may be different in healthy subjects than in subjects with spinal cord injury (SCI), submitted to an altered integration of body afferent inputs. In this randomized, double-blind, sham-controlled trial, we recruited 22 subjects with SCI assigned to either real (n = 11) or sham (n = 11) rTMS and nine healthy subjects, who served as control group, receiving both real (at 20 Hz, with double cone coil over vertex) and sham rTMS separated by at least one week. We recorded the blink reflex (BR) to supraorbital nerve (SON) electrical stimulation and its modification by another conditioning SON, to study the BR excitability recovery (BRER), or a prepulse electrical stimulus to the right index finger, to study the BR inhibition by prepulse (BRIP). Subjects were examined immediately before and after either sham or real rTMS. Real but not sham rTMS significantly reduced the area of the BR R2 response in both SCI and healthy subjects. There were no changes in BRER and BRIP. rTMS over the vertex modulates brainstem reflexes with no significant differences between SCI and healthy subjects.